Cyber attacks on hospitality sector: stock market reaction. (25th June 2020) - Arcuri, Maria Cristina; Gai, Lorenzo; Ielasi, Federica; Ventisette, Elisabetta
Abstract : Purpose: The paper aims to analyze the impact of cyber attacks on stock returns of companies operating in the hospitality sector. The fast development of information and communication technologies has been posited as both an opportunity and a challenge to the United Nations Global Sustainable Development Goals. Digital technologies are significant tools for sustainable development, but if they are not addressed appropriately, they can potentially hinder the progress toward sustainability. Among negative impacts, it is necessary to consider cyber risk, a major concern today, in particular for industries which work with sensitive data, such as tourism businesses. Hospitality businesses have to adequately manage cyber insecurity and digital privacy issues, to prevent losses and contribute to socioeconomic sustainable growth. Design/methodology/approach: Using event-study methodology, the paper provides empirical evidence on the effect of announcements of 170 information security breaches on the market value of firms operating in the hospitality sector in the past five years. Findings: The study focuses on identifying potential threats of cyber attacks for the economic value of listed companies. The authors find that negative market returns occur following announcements of cyber attacks suffered by hospitality companies. Adequate investments in technology for cyber security and staff training are relevant in the hospitality sector to reduce cyber risk. Originality/value: The paper contributes to identifying potential threats of cyber attacks for the economic value of listed companies operating in the hospitality sector. The analysis is carried out by collecting an original sample of global cyber attacks from newspaper announcements sourced from the LexisNexis database. Abstract : 论酒店业的网络攻击：股票市场的反应 研究目的: 信息通讯技术的快速发展, 对UN全球可持续发展战略目标带来机遇和挑战。电子技术对可持续发展起到重要作用, 但是如果它们未被合理使用, 则对可持续性构成潜在威胁。在众多负面影响中, 网络攻击不可忽视, 成为现今重大担忧, 尤其是对于处理敏感数据的行业, 比如旅游产业。酒店业必须具备管理网络安全和处理电子隐私的能力, 以防止损失, 对社会经济可持续增长做出贡献。 研究设计/方法/途径: 本论文分析酒店业内因网络攻击而遭受股票的影响。借用事件分析法, 本论文研究了近五年来, 170项信息安全泄露消息对酒店市场价值的影响。 研究结果: 本论文主要确立了上市公司因网络攻击而受到的经济价值影响。我们发现, 酒店公司在宣布网络攻击后, 其市场收益受到负面影响。充足的网络安全技术投入和人员培训与酒店减少网络攻击有一定的联系。 研究原创性/价值: 本论文分析了酒店业中上市公司因网络攻击而带来的潜在经济价值的损失。研究分析样本来自Lexis Nexis数据库中的全球网络攻击的新闻报道。